Painful Ophthalmoplegia Manifesting with Third Nerve Palsy in Childhood - Bengü Ekinci Kökteki; Şansal Gedik; Berker Bakbak (Türk Oftalmoloji Dergisi, 2012)
The causes of painful ophthalmoplegia that manifests with third nerve palsy in childhood include postinfectious third nerve palsy, compressive lesions, vascular anomalies and ophthalmoplegic migraine. Ophthalmoplegic migraine is a rare pathology in the literature and is characterized by recurrent attacks of headache and ophthalmoplegia that usually begins during childhood. Ophtalmoplegia occurs due to paresis or paralysis of cranial nerves 3, 4 or 6. Attacks may last a few hours to weeks and usually are recovered with appropriate therapy, but some cases may demonstrate permanent defects. In this paper, we discuss the case of an 11-year-old patient, who was admitted to our outpatient clinic with the complaints of right ptosis, mydriasis and severe headache. Ophthalmologic examination revealed oculomotor nerve palsy, the patient was diagnosed as having ophthalmoplegic migraine and medical treatment was started. Her complaints have regressed with medication for migraine and recovered completely in 8 weeks. In this case report, painful ophthalmoplegia during childhood and its possible causes are discussed. (Turk J Ophthalmol 2012; 42: 159-62)